Home visit and nursing students: importance for the family and community - Silvestre, Mirele Estrela; Oliveira, Nayara Kallynne Cavalcante de; Gomes, Sarah Yasmin Lucena; Alves, Selda Gomes de Sousa; Sousa, Milena Nunes Alves de (Revista de Enfermagem UFPE on line, 2011)
ABSTRACT Objective: <span style="font-family: ";Trebuchet MS";,";sans-serif";; color: black; font-size: 9pt; mso-bidi-font-weight: bold; mso-bidi-font-style: italic; mso-fareast-language: PT-BR; mso-ansi-language: EN-US;" lang="EN-US">to identify the knowledge of the nursing students about the importance of Home Visits (HV) for family and community. Method: we performed exploratory, descriptive, with quantitative approach. After approval by the Ethics Committee in Research of Santa Maria College, via the protocol number: 422022010, 85 nursing students (53.8% of the universe) answered a questionnaire in May of 2010. Results: the sample was composed mostly by women who knew about the meanings of the HV. As for the importance of the theme and concept, most of the students indicated the completeness of family and community care through an action taken in residence. Still, 98.8% of subjects reported that the HV can help improve the living conditions of families and communities. Conclusion: well, based on data collected, the importance of HV for families and communities is seen as an instrument of home care, in order to more closely meet the real needs presented by and/or communities, and help provide improvements in living conditions. Descriptors: home visits; perception; student nurses. RESUMO Objetivo: identificar o conhecimento dos estudantes de enfermagem acerca da importância da Visita Domiciliar (VD) para a família e comunidade. Método: foi realizada pesquisa exploratória, descritiva, com abordagem quantitativa. Após aprovação do Comitê de Ética em Pesquisa da Faculdade Santa Maria, através do protocolo de nº 422022010, 85 estudantes de enfermagem (53,8% do universo) responderam a um questionário em maio de 2010. Resultados: a amostra foi composta, na maioria, por mulheres conhecedoras dos significados sobre a VD. Quanto à importância e conceituação da temática, a maioria dos estudantes apontou a integralidade dos cuidados familiares e comunitários, através de uma ação realizada em domicilio. Ainda, 98,8% dos sujeitos afirmaram que a VD pode ajudar a melhorar as condições de vida das famílias e comunidades. Conclusão: assim, com base nos dados coletados, a importância da VD para as famílias e comunidades é entendida como um instrumento do cuidado domiciliar, com intuito de conhecer mais de perto as reais necessidades apresentadas pelas e/ou comunidades, além de ajudar a proporcionar melhorias das condições de vida. Descritores: visita domiciliar; percepção; estudantes de enfermagem. RESUMEN Objectivo: identificar el conocimiento de los estudiantes de enfermería sobre la importancia de la visita domiciliaria (VD) para la familia y la comunidad. Método: se realizó un estudio exploratorio, descriptivo y cuantitativo. Después de la aprobación por el Comité de Ética de la Facultad Santa María, por el protocolo N° 422022010, 85 estudiantes de enfermería (53,8% del universo) respondieron a un cuestionario en mayo de 2010. Resultados: la muestra estuvo constituida principalmente por mujeres conocen el significado de la VD. En cuanto a la importancia y el concepto del sujeto, la mayoría de los estudiantes indica la integridad de la atención familiar y comunitaria a través de una acción realizada en su residencia. Sin embargo, el 98,8% de los sujetos informó de que la VD puede ayudar a mejorar las condiciones de vida de las familias y comunidades. Conclusión: por lo tanto, con base en los datos recogidos, la importancia de la DV para las familias y las comunidades se ve como un instrumento de asistencia a domicilio, a fin de satisfacer mejor las necesidades reales presentadas por y/o comunidades, y ayudar a proporcionar mejoras en las condiciones de vida. Descriptores: visita domiciliaria; percepción; estudiantes de enfermería.